Pengelolaan Perkembangan Emosional Anak Usia Dini Dalam Pembelajaran Secara Daring Di Masa Pandemi Covid-19 - Harahap, Masyitah Addina; Wahyuni, Wahyuni; Khadijah, Khadijah (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2021)
This study aims to analyze the management of early childhood emotional development in online learning during the COVID-19 pandemic at the PAUD level. The research methodology used is descriptive qualitative with a library research approach. Data analysis and data collection techniques were obtained from mainly books and journals. The results found can be concluded that it takes cooperation between teachers, parents and children, the aim is to help manage good emotional development in children. The ability to manage children's emotions is seen from how big the role of parents in managing children's emotions from home and the ability of teachers to prepare learning well and in accordance with the needs of children at the PAUD level to learn comfortably as well as honest and disciplined attitudes from children in completing their tasks. Suggestions in this study should be for future research to generalize through broader and in-depth research related to emotional management of early childhood, because good emotional development from an early age will help form good social interaction communication.